2018
DOI: 10.5271/sjweh.3775
|View full text |Cite
|
Sign up to set email alerts
|

Systematic literature review on the effects of occupational safety and health (OSH) interventions at the workplace

Abstract: This meta-analysis showed moderately strong evidence for improvement by occupational health and safety (OHS) legislation and inspections with respect to injuries and fatalities, while limited evidence is available for effects of training, campaigns and introduction of technical devices. Studies of intervention targeted at reducing psychological and musculoskeletal disorders are few and inconclusive. Further studies of the effect of OHS interventions are strongly warranted. Affiliation:Refers to the following t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
57
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(59 citation statements)
references
References 44 publications
1
57
0
1
Order By: Relevance
“…Nevertheless, regarding intervention on small enterprises, a review of studies published before 2006 reported a lack of evaluation, in terms of both effect and practical applicability. The most effective preventive approaches seemed to be simple and low-cost solutions, disseminated through personal contact [ 21 ]. A later systematic review was undertaken to identify effective interventions to improve HSW conditions in small businesses.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, regarding intervention on small enterprises, a review of studies published before 2006 reported a lack of evaluation, in terms of both effect and practical applicability. The most effective preventive approaches seemed to be simple and low-cost solutions, disseminated through personal contact [ 21 ]. A later systematic review was undertaken to identify effective interventions to improve HSW conditions in small businesses.…”
Section: Discussionmentioning
confidence: 99%
“…There are even comparative studies that have found an inverse relationship between union strength and occupational accident levels among European countries [22][23][24]. More recent research would go some way to criticizing approaches that focus solely on studying the direct relationship between the presence of collective representation in companies and risk prevention document management or its impact on reducing incidence rates for accidents at work [25][26][27][28]. These studies from a holistic perspective seek to understand both the external and internal determinants of the workplace that influence the effectiveness of worker participation.…”
Section: Introductionmentioning
confidence: 99%
“…These studies from a holistic perspective seek to understand both the external and internal determinants of the workplace that influence the effectiveness of worker participation. In this sense, the following external determinants can be identified: macrocontextual factors, related to policies and systems of legal regulation of occupational health [28,29], such as the capacity of representatives and workers to paralyze productive activity in the face of serious or imminent risk [30]; the promotion of regulations that reward the integration of the prevention management system through its own means to facilitate participation [31]; the promotion of participation through the requirements of the labour inspection [32], regulations that do not systematically make technicians responsible for the prevention of accidents in companies to prevent expert knowledge from blocking participation [33]; or the promotion of policies for the representation of interests that facilitate decentralised self-regulation through the participation of autonomous trade unions [27,34]. The internal factors that influence the effectiveness of participation are business leadership and willingness to promote a participatory culture [35][36][37][38][39][40]; training and empowerment of workers and their representatives to collectively challenge unsafe situations [37][38][39]; the size of the workplace and the sector of activity to the extent that participation is greater in larger workplaces and in industries where occupational risks are more evident [18,27,41]; in addition, greater capacity for participation will exist when specialized occupational health representation is unionized [42] or has strong external support from the union [43,44].…”
Section: Introductionmentioning
confidence: 99%
“…Further, Robson et al reviewed articles on the effectiveness of occupational health and safety management system interventions and found that only 1 of 23 articles described an intervention study with a sufficiently high methodological quality (35). Moreover, in the review of OSH interventions by Andersen et al (6) the authors concluded that the overall quality of evidence was limited and at best moderate, and Roeloef et al (36) reviewed control strategies for chemical hazards published during 1993-1999 and showed that intervention effectiveness was not consistently evaluated. The general low study quality in our review and in mentioned reviews is possibly related to common difficulties in executing high quality intervention studies in the occupational field.…”
Section: Discussionmentioning
confidence: 99%